Proceedings of the 10th Hydrogen Technology Convention, Volume 1 WHTC 2023, 22-26 May, Foshan, China - Sun, Hexu.; Pei, Wei.; Dong, Yan.; Yu, Hongmei; You, Shi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book highlights the latest advances in fundamental research, technologies and applications of hydrogen energy and fuel cells. In recent years, energy conversion between electricity and hydrogen energy has attracted increasing attention as a way to adjust the load of the grid. This book discusses and exchanges cutting-edge findings and technological developments in fields such as new proton exchange membrane electrolyzers, new electrode materials and catalysts, renewable energy, off-grid/grid-connected water electrolysis for hydrogen production, key materials and components of fuel cells, high-temperature solid oxide water electrolysis, energy storage technologies and research, CO2 hydrogenation to methanol, nitrogen to ammonia and other applications with industrial potential. The main topics of the proceedings include: 1) Policies and strategies for hydrogen energy and fuel cells; 2) Advanced proton exchange membranes, electrodes and catalyst materials for water electrolysis; 3) Advanced hydrogen compression, storage, transportation and distribution technologies; 4) Safety and related standards; 5) Manufacture and R&D of key materials and components of fuel cells and stack systems.
Hydrogen Energy and Fuel Cell Industry Policy and Strategy -- Hydrogen Production and Purification -- Hydrogen Compression, Storage, Transport and Distribution -- Hydrogen Safety, Standards and Management -- Hydrogen Energy Applications: Transportation, Power Generation, Heating; Metallurgy, Chemical Industry; Industrial Application -- Fuel Cells: Key Materials; Key Components; Stacks, System Manufacturing and R&D.
Keywords: Hydrogen as fuel; Thermodynamics; Soft condensed matter; Fuel cells; Materials; Security systems; Automotive engineering; Hydrogen Energy; Thermodynamics; Fluids; Fuel Cells; Security Science and Technology; Automotive Engineering